Tribological and dynamical analysis of a brake pad with multiple blocks for a high-speed train. (November 2020) - Wu, YK; Mo, JL; Tang, B; Xu, JW; Huang, B; Xiang, ZY; Zhou, ZR
In this research, the tribological and dynamical characteristics of a brake pad with multiple blocks are investigated using experimental and numerical methods. A dynamometer with a multiblock brake pad configuration on a brake disc is developed and a series of drag-type tests are conducted to study the brake squeal and wear behavior of a high-speed train brake system. Finite element analysis is performed to derive physical explanations for the observed experimental phenomena. The experimental and numerical results show that the rotational speed and braking force have important influences on the brake squeal; the trends of the multiblock and single-block systems are different. In the multiblock brake pad, the different blocks exhibit significantly different magnitudes of contact stresses and vibration accelerations. The blocks located in the inner and outer rings have higher vibration acceleration amplitudes and stronger vibration energies than the blocks located in the middle ring.